1993
DOI: 10.1126/science.7687073
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Gene Expression After Intravenous DNA Delivery into Adult Mice

Abstract: Direct gene transfer into adult animals resulting in generalized or tissue-specific expression would facilitate rapid analysis of transgene effects and allow precise in vivo manipulation of biologic processes at the molecular level. A single intravenous injection of expression plasmid:cationic liposome complexes into adult mice efficiently transfected virtually all tissues. In addition to vascular endothelial cells, most of the extravascular parenchymal cells present in many tissues including the lung, spleen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
296
0
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 723 publications
(307 citation statements)
references
References 20 publications
8
296
0
3
Order By: Relevance
“…25 Although the level of gene expression varies from study to study, the lung invariably shows the highest level of expression. [12][13][14][26][27][28][29] In addition, Li et al 29 compared intravenous and intraportal injection of cationic liposome/ protamine/DNA (LPD) and demonstrated that the gene expression in the lung was still higher than that in liver, even when the intraportal route was used. In contrast to this, intravenous and intraportal administration of Man-C4-Chol/DOPE(6:4) and Man-C4-Chol/DC-Chol/DOPE (3:3:4) liposome/DNA complexes resulted (with one exception) in higher gene expression in the liver than in the lung and spleen, suggesting that selective and efficient delivery of plasmid DNA to liver is achieved by these carriers (Figures 5 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…25 Although the level of gene expression varies from study to study, the lung invariably shows the highest level of expression. [12][13][14][26][27][28][29] In addition, Li et al 29 compared intravenous and intraportal injection of cationic liposome/ protamine/DNA (LPD) and demonstrated that the gene expression in the lung was still higher than that in liver, even when the intraportal route was used. In contrast to this, intravenous and intraportal administration of Man-C4-Chol/DOPE(6:4) and Man-C4-Chol/DC-Chol/DOPE (3:3:4) liposome/DNA complexes resulted (with one exception) in higher gene expression in the liver than in the lung and spleen, suggesting that selective and efficient delivery of plasmid DNA to liver is achieved by these carriers (Figures 5 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of plasmid carriers leads to interactions with plasma proteins and accumulation of genes into undesired locations, mostly in the lung and liver. 8,26,27 This leads to poor delivery to the desired target tissues. Local gene transfer with a small amount of plasmid DNA should reduce systemic spread of plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic liposomes are the most commonly used nonviral delivery system for delivery of plasmids into cells in vitro [1][2][3] and in vivo. [4][5][6] A significant problem associated with cationic liposomes is their low in vivo transfection efficiency, 7,8 possibly due to inactivation of the liposomes by serum. 9,10 Despite this limitation, cationic liposome carriers have several major advantages such as relative ease of large-scale production and minimal toxicity.…”
Section: Introductionmentioning
confidence: 99%